Hardware development of a UPQC in a power distribution system-part II - Ng, Tiong Wee. (2010)
The extensive use of advance power electronics devices and non-linear loads can be found in many industrial or commercial applications in the recent years. Therefore, harmonics distortion to the voltage and current supply is evident. This has raised major concerns over the power quality in the power distribution system, which may lead to malfunction, overheating or damage of sensitive equipment. This project aims to discuss and identify the control strategy for Unified Power Quality Conditioner (UPQC) with integration of series and shunt active filters. The control system regulates the load voltage and source current to the desired reference in the existence of harmonics components. This is based on the state space model computed and developed by the UPQC. The derivation of the UPQC system is described in details. In the preceding project, the hardware experimental setup has been developed. The components mainly consist of the AC power supply, Voltage Source Inverter (VSI), Pulse Width Modulation (PWM) module, DC driver circuit, filters, voltage and current transducers. They are interfaced to DS1104 R&D Controller Board to perform the control system through UPQC hardware implementation on Matlab application. Previously, it has identified the Controller Board is unable to meet the high computational requirement of the UPQC with Kalman Filter. Therefore, it derives the motivation to testify the control system without the implementation of the Kalman filter. This project is conducted based on single-phase distribution system. Simulation and hardware experimental studies are presented to verify the various theories.